2012
DOI: 10.1210/jc.2012-1440
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-Müllerian Hormone Levels in Healthy Females: A Nomogram Ranging from Infancy to Adulthood

Abstract: During infancy AMH levels increase, whereas during adolescence, a plateau until the age of 25 yr was observed. From the age of 25 yr onward, serum AMH levels correlate inversely with age, implying that AMH is applicable as a marker of ovarian reserve only in women of 25 yr old and older. Our nomogram may facilitate counseling women on their reproductive potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
94
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(103 citation statements)
references
References 37 publications
7
94
2
Order By: Relevance
“…Larger cohorts are necessary to study this association in the future. In healthy females, AFC and AMH correlate very well (39), but this study shows that this correlation is weak among CCS. This may be due to the fact that follicular AMH expression is lower in CCS treated with gonadotoxic therapies.…”
Section: Discussioncontrasting
confidence: 56%
“…Larger cohorts are necessary to study this association in the future. In healthy females, AFC and AMH correlate very well (39), but this study shows that this correlation is weak among CCS. This may be due to the fact that follicular AMH expression is lower in CCS treated with gonadotoxic therapies.…”
Section: Discussioncontrasting
confidence: 56%
“…The AMH levels that were observed in our study are slightly higher than those previously reported in studies performed in adult women with PCOS [25, 27-30]. This difference may be partially explained by the fact that higher AMH levels are found in younger women than in older women [31, 32]. A recent publication by Lie Fong et al [33] used cluster analysis to define the AMH threshold levels for the diagnosis of PCOM and showed that higher serum AMH levels should be used in young women.…”
Section: Discussioncontrasting
confidence: 76%
“…In addition, this patient was treated with cyclophosphamide, which has clearly been shown to reduce ovarian reserve 24,25 . In fact, this child’s AMH levels indicated diminished ovarian reserve comparable to that of an adult female towards the end of her reproductive life 26 . Therefore, the presence of apparently normal ovarian function at the completion of chemotherapy and menarche should not be interpreted as evidence of lack of gonadal damage from chemotherapy.…”
Section: Discussionmentioning
confidence: 82%